2013
DOI: 10.1038/srep02464
|View full text |Cite
|
Sign up to set email alerts
|

Two mixed-NH3/amine platinum (II) anticancer complexes featuring a dichloroacetate moiety in the leaving group

Abstract: Two mixed-NH3/amine platinum (II) complexes of 3-dichoroacetoxylcyclobutane-1, 1-dicarboxylate have been prepared in the present study and characterized by elemental analysis and IR, HPLC-MS and 1H, 13C-NMR. The complexes exist in equilibrium between two position isomeric forms and undergo hydrolysis reaction in aqueous solution, releasing the platinum pharmacophores and dichloroacetate which is a small-molecular cell apoptosis inducer. Both complexes were evaluated for in vitro cytotoxic profile in A549, SGC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…It has been reported that the Pt(II) anticancer drug cycloplatam, important for overcoming drug resistance to cisplatin (Chart 4), occurs in two isomeric cis / trans forms, the biological activity of any single isomeric form remaining at first unknown. Recently, the two bioactive isomers have been separated and tested showing equal anticancer activity …”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the Pt(II) anticancer drug cycloplatam, important for overcoming drug resistance to cisplatin (Chart 4), occurs in two isomeric cis / trans forms, the biological activity of any single isomeric form remaining at first unknown. Recently, the two bioactive isomers have been separated and tested showing equal anticancer activity …”
Section: Resultsmentioning
confidence: 99%
“…Ruthenium (Ru) complexes have attracted much attention as building blocks for novel metal-based anticancer and antimetastatic drugs since the discovery of cisplatin and the successful application of other platinum (Pt) complexes 8 9 10 . During the past three decades, a large number of potential Ru complexes have exhibited utility in chemotherapy, and some of them, including NAMI-A and KP1019, have entered into human clinical trials 8 11 .…”
mentioning
confidence: 99%
“…Introduction of a dichloroacetate moiety into cyclobutane-1,1-dicarboxylic acid had been previously described in our report [18]. Shortly, K 2 PtCl 4 was first converted to K 2 PtI 4 in situ by the treatment with KI, followed by addition of 2NH 3 or diamines, forming an insoluble diam(m)inediiodoplatinum(II) intermediate.…”
Section: Synthesis and Characterizationmentioning
confidence: 92%
“…3-Dichoroacetoxylcyclobutane-1,1-dicarboxylic acid and (4R,5R)-4,5-bis(aminomethyl)-2-isopropyl-1,3-dioxolane were prepared as previously described [18,19]. All other chemicals obtained from commercial suppliers were of analytical grade and used as received.…”
Section: Materials and Instrumentmentioning
confidence: 99%
See 1 more Smart Citation